KEPASTIAN HUKUM DALAM PERKARA PERCERAIAN TERHADAP SALAH SATU PIHAK YANG TIDAK DIKETAHUI KEBERADAANNYA: ANALISIS PUTUSAN NOMOR 5924/PDT.G/2022/PA.SBR - R. Fahmi Natigor Daulay; Ade Sultan Muhammad (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
Divorce decided by default judgment against a party whose whereabouts are unknown raises issues of legal certainty and rights protection. Research on the Religious Court of Sumber Decision Number 5924/Pdt.G/2022/PA.Sbr using normative legal methods shows that formally the decision has complied with procedural law provisions. However, from a material aspect, there are still weaknesses in summons transparency, protection of respondent's rights, and application of the precautionary principle. Strengthening summons standards, optimizing the ex officio role of judges, and regulatory updates are needed to achieve a balance between judicial efficiency, legal certainty, and substantive justice in default divorce cases in Religious Courts.